Advancing a Model of Secondary Trauma: Consequences for Victim Service Providers. Issue 7 (April 2021) - Ellis, Colter; Knight, Kelly E.
A burgeoning body of scholarship is attempting to understand, normalize, and ameliorate the emotional strain of victim service provision. The literature, however, has yet to fully theorize the hazardous process of empathetic engagement with victims. As a result, concepts, mechanisms, and outcomes are often conflated, making it difficult to understand the etiological path of this occupational risk. The goal of this article is to attend to this gap by accomplishing three objectives. The first is to engage with the perspective of symbolic interaction to theoretically ground a conceptual model of secondary trauma. The second objective is to propose a model of secondary trauma that acknowledges its inherently interactional, interpretive, and, thus, vicariously transmissible nature. The third objective is to begin the work of empirically supporting this model with data from a sample of victim service providers ( n = 94) collected using in-depth interviews, focus groups, ethnographic participant observation, and community-based participatory research. Our findings suggest that victim service provision, in the form of empathetic engagement, can blur the boundary between self and other, and lead to a sense of damage in the self that manifests in unreliable self-agency, untrustworthy coherence of other, desensitized self-affectivity, and fractured self-history. This work has significant implications. We illustrate an important paradox by showing how victim service provision can be helpful to victims but harmful to providers. We also offer a pathway for reducing this harm. By specifying mechanisms of damage, the model can be used to inform policies and practices supportive of victim service providers' health and well-being.